Mu'tazilite Interpretation of Allah-Human Relationship in the Framework of Grace Theory - Aytepe, Mahsum (DINBILIMLERI AKAD ARASTIRMA MERKEZI, 2017)
Human is created by Allah, the Lord of the worlds, and is held responsible for the offer. Proposal is both a responsibility and an opportunity for man. The thing that turns the proposal into a possibility is that it is the subject of Allah's help and grace. Mu'tazila explains Allah's help with the concept of grace. Grace refers to the divine help as long as man is obliged. Man, both being subjected to a proposal which was assisted grace and can preserve his freedom as well. The main problem here is how the Mu'tazila, who accepts the freedom of man unquestioningly, will explain this help. Because the Mu'tazila does not accept that the will and the preference of the human being are damaged in any way. This study refers to the real relationship between God and man in the context of the theory of grace, and explains how Mu'tazilian gives an explanation for the paradox of help and freedom.
Keywords: Mu'tazila; Qadi Abd al-Jabbar; Grace; Proposal; Ethic